Obesity and Mental Health: A Longitudinal, Cross-Cultural Examination in Germany and China - Lavallee, Kristen L.; Zhang, Xiao Chi; Schneider, Silvia; Margraf, Jürgen (Frontiers in Psychology, 2021)
The present study examines the relationship between obesity and mental health using longitudinal data. Participants with data at baseline and one-year follow-up were included from two countries: Germany (364) and China (9007). A series of structural equation models with three mediators and one moderator were conducted separately for female and male students in Germany and China. Zero-order correlations indicated that overweight/obesity was significantly related to later depression and anxiety in Chinese males. Additional effects of obesity on later mental health flowed through effects on attractiveness (Chinese and German females, and Chinese males), physical health (Chinese males), and life satisfaction (German females). Though overweight/obesity is related to mental health across many other studies, results in this study yield total effects between overweight/obesity and follow-up mental health only in Chinese males. The relationship between overweight/obesity and follow-up mental health was significantly mediated by follow-up attractiveness, or health state, or life satisfaction in German females, Chinese females, and Chinese male students, with no significant indirect effects found in German male students. This highlights the possible importance of culture in examining these effects.